PHYSICAL QUALITIES DEVELOPMENT IN THE SPORTS ACTIVITIES PROCESS - Dustov Djonibek Amriddinovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the strength and speed, endurance, flexibility, agility, physical qualities and physical qualities developing methods in the sports activities process.